(untitled) (Bangladesh Journal of Medical Science, 2012)
Introduction: Subtrochateric femoral fracture is a major cause of morbidity and mortality in patients with lower extremity injuries. There have been no studies that have specifically looked at the management of subtrochanteric femoral fractures in skeletally immature adolescents. It was the purpose of this study to investigate the treatment of this injury in this unique patient population. Methods: This study was conducted in the Department of Orthopaedic surgery in M. M. Medical College from July 2006 to November 2008. Thirty-four patients were recruited from Emergency and out patient department having closed subtrochanteric femoral fracture. All patients were operated under general or spinal anesthesia. All patients were followed for twelve months. Results: All children achieved union in a mean time of 10 weeks (range from 6 - 16 weeks) depending on the type of long bone. Full weight bearing was possible in a mean time of 8.8 weeks. Mean duration of hospital stay was 9.8 days. The mean follow-up period was 28 months (17-48 months). Complications were recorded in 4 (11.77%) patients and included: two entry site skin irritations, one protrusion of the wires through the skin and one delayed union. The results were excellent in 97.06% and good in 2.97% patients. Conclusions: We conclude that Rigid and close interlocking nailing between the age of 9-16 years offered excellent fracture stability allowing early mobilization (early weight bearing) and joint motion in comparisons to the other groups and between the age of 6-8 years titanium elastic nail and bridging plate offered excellent result. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11718 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12